Silicon-carbon composite electrode, preparation method thereof and chemical power supply adopting silicon-carbon composite electrode

By designing a silicon-carbon composite electrode structure with a silicon-carbon inner layer, a support buffer middle layer and an active substance outer layer, and using rolling technology, the problem of expansion of existing silicon-carbon electrodes during circulation is solved, and the chemical power supply is improved Cyclic performance.

CN119400804APending Publication Date: 2025-02-07SHANGHAI AOWEI TECH DEV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511136.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing silicon-carbon composite electrodes still have obvious expansion during the cycle, affecting the cycling performance of chemical power supplies.

Method used

Design a silicon-carbon composite electrode structure, including silicon-carbon inner layer, support buffer middle layer and active substance outer layer, the middle layer forms a network structure, and some active substance outer layer is embedded in the middle layer network, and the compaction density of the electrode is adjusted through rolling technology .

Benefits of technology

Through this design, the expansion rate of the silicon-carbon composite electrode is reduced, and the cycling performance of the chemical power supply is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400804A_ABST
    Figure CN119400804A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of negative electrode materials, and particularly relates to a silicon-carbon composite electrode, a preparation method of the silicon-carbon composite electrode and a chemical power source prepared by adopting the silicon-carbon composite electrode. The silicon-carbon inner layer is arranged on the current collector; the supporting buffer middle layer is arranged on the silicon carbon inner layer; the active material outer layer is arranged on the supporting buffer middle layer; wherein the compaction density of the supporting and buffering middle layer is smaller than that of the active substance outer layer, the supporting and buffering middle layer forms a network structure, and part of the active substance outer layer is embedded into the network structure. The method has the advantages that the carbon nanotubes form a long-range conductive network, so that the conductivity is improved; the water-based binder and the silicon-carbon material form a hydrogen bond, so that the binding performance is enhanced, and the silicon-carbon inner layer expansion is inhibited; the outer layer active substance is partially embedded into the middle layer network and partially covers the surface of the middle layer network, and during rolling, the outer layer active substance forms a buffer area with large porosity due to the supporting effect of the middle layer carbon-based material, and electrode expansion is further inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials, and in particular relates to a silicon-carbon composite electrode, a preparation method thereof, and a chemical power source prepared by using the electrode. Background Art

[0002] In recent years, due to the increasingly prominent energy crisis and pollution problems caused by the accelerated consumption of traditional energy, the development and research of various new energy sources including solar energy, wind energy, nuclear energy, bioenergy and other green energy have gradually shown their important strategic significance. With the rapid development of electric vehicles and large-scale energy storage equipment, the requirements for energy storage devices that play a key role in them are getting higher and higher. High energy density, long cycle life and high safety are the main indicators pursued during the next generation of energy storage. Among them, lithium-ion batteries and lithium-ion capacitors are the two most promising chemical power sources.

[0003] The negative electrode of these two types of chemical power sources can use graphite as the active material, but the capacity of graphite is close to its theoretical capacity (375mAh / g), and it is difficult to further increase it. In addition, the lithium insertion potential of graphite is very close to the lithium deposition potential, and lithium deposition is very likely to occur under fast charging and low temperature conditions, causing safety hazards. Therefore, exploring high-performance negative electrode materials is one of the keys to improving the performance of devices.

[0004] Silicon-based materials are considered to be the most promising negative electrode materials for lithium-ion batteries. Their advantages are theoretical specific capacity of up to 4200mAh / g, which is 10 times that of graphite, and low lithium de-potential of 0.4V. However, the biggest disadvantage of pure silicon negative electrode materials is that silicon undergoes huge volume changes during the process of lithium ion extraction / insertion. After being fully embedded with lithium ions, the volume expansion can reach 300%. The volume deformation and stress generated during repeated extraction and insertion will cause the material to pulverize, resulting in poor contact and continuous generation of new SEI films, thereby consuming electrolyte. In order to overcome these defects of pure silicon negative electrode materials in lithium-ion battery applications and improve the performance of lithium-ion batteries, researchers have conducted a variety of improvement studies, including nano-sizing of silicon, synthesis of silicon oxide, synthesis of silicon / metal alloys, and surface carbon coating of silicon materials. Among them, silicon oxide and carbon-coated silicon-carbon materials have entered the early stages of commercialization, and silicon-carbon materials with higher specific capacity are also the "must-fight" for various negative electrode manufacturers, including BYD, Shanshan Co., Ltd., etc., which have achieved mass production and shipment of silicon-carbon negative electrodes.

[0005] Although carbon coating increases the electronic conductivity and ionic conductivity of the negative electrode material, it can only buffer the stress caused by volume deformation during the cycle to a certain extent. Therefore, the current commercialization process is more commonly used to mix silicon-carbon materials with carbon active materials such as graphite in a certain proportion and then prepare them into electrodes. The specific capacity of existing commercial silicon-carbon electrodes is between 1500 and 2000mAh / g. Mixing it with a graphite negative electrode in a certain proportion can achieve a specific capacity of more than 400mAh / g, which has significantly improved efficacy compared to the graphite negative electrode and can further improve the energy density of the device. However, due to the characteristics of silicon-carbon materials, the composite electrode will still have obvious expansion during the cycle. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a silicon-carbon composite electrode and a preparation method thereof and a chemical power source using the silicon-carbon composite electrode, so as to reduce the expansion of the silicon-carbon composite electrode to a certain extent and improve the cycle performance of the chemical power source.

[0007] In order to achieve the above-mentioned purpose, a silicon-carbon composite electrode is designed, comprising: a current collector; a silicon-carbon inner layer arranged on the current collector; a supporting buffer middle layer arranged on the silicon-carbon inner layer; an active material outer layer arranged on the supporting buffer middle layer; wherein the compaction density of the supporting buffer middle layer is less than the compaction density of the active material outer layer, and the supporting buffer middle layer forms a network structure, and part of the active material outer layer is embedded in the network structure.

[0008] Preferably, the silicon-carbon inner layer is completely coated on the current collector and is composed of a silicon-carbon material, a conductive agent, and a binder. The silicon-carbon material includes one silicon-carbon material or a combination of multiple silicon-carbon materials, wherein the content of silicon element in each silicon-carbon material does not exceed 50%, and the proportion of the silicon-carbon material to the total active substance is ≤30%. The conductive agent includes carbon nanotubes or carbon black or a combination of the above. The binder is an aqueous binder, and the solvent used is deionized water; the carbon black includes conductive carbon black, Ketjen black, acetylene black or any combination of the above. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes or any combination thereof. The aqueous binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane or any combination of the above.

[0009] Preferably, the supporting buffer middle layer is composed of a carbon-based material, a conductive agent, and a binder. The carbon-based material includes hard carbon, soft carbon or any combination thereof. The compaction density of the carbon-based material is ≥ the silicon carbon used in the silicon carbon inner layer and is less than the active material used in the active material outer layer. The conductive agent includes carbon nanotubes, carbon black or any combination thereof. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes or any combination thereof. The carbon black includes conductive carbon black, Ketjen black, acetylene black or any combination thereof. The binder includes a water-based binder and an oil-based binder.

[0010] Preferably, after coating, the supporting buffer middle layer presents a dense network structure, including a transverse network and a longitudinal network. The coating rate of the supporting buffer middle layer network is ≤50%, and the coating rate of the supporting buffer middle layer network is the total coating area of ​​the middle layer / total coating area of ​​the inner layer; the water-based binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane or any combination thereof, and the oil-based binder includes polyvinylidene fluoride, polyimide, perfluorosulfonic acid ionomer or any combination thereof.

[0011] Preferably, the coating amount of the supporting buffer middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * maximum expansion rate of inner layer silicon carbon * compaction density of middle layer material * coating rate of middle layer network.

[0012] Preferably, the outer layer of the active material is composed of an active material, a conductive agent, and a binder. The active material includes graphite, soft carbon, and mesophase carbon microspheres. The conductive agent includes carbon nanotubes, carbon black, or any combination thereof. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes, or any combination thereof. The carbon black includes conductive carbon black, Ketjen black, acetylene black, or any combination thereof. The binder includes an aqueous binder and an oil-based binder. The aqueous binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane, or any combination thereof. The oil-based binder includes polyvinylidene fluoride, polyimide, perfluorosulfonic acid ionomer, or any combination thereof.

[0013] Preferably, the outer layer of active material is composed of active material with a higher compaction density than the supporting buffer middle layer, and the coating amount of the outer layer = the designed total coating amount of the electrode - the coating amount of the inner layer - the coating amount of the middle layer.

[0014] The present invention also provides a method for preparing a silicon-carbon composite electrode, comprising the following steps: S1. Preparation of inner layer: Mix silicon-carbon material, conductive agent and binder in a mass ratio of (60~97.5%): (0.5~30%): (2~10%), apply to both sides of the current collector, the current collector is copper foil, and the inner layer preparation is completed after drying; S2. Preparation of middle layer: Mix carbon-based material, conductive agent and binder in a mass ratio of (90~99%): (0~5%): (1~5%), apply intermittently to both sides of the pole piece for inner layer preparation, and complete the preparation of middle layer after drying. The coating nozzle for coating the middle layer can be designed as an intermittent nozzle, and the coating nozzle has Function of intermittent coating; S3. Preparation of outer layer: Mix the active material, conductive agent and binder in a mass ratio of (90~98.5%): (0.5~5%): (1~5%), and apply them on both sides of the electrode sheet with the middle layer prepared. During the coating process of the outer layer electrode sheet, the active layer slurry is partially embedded in the middle layer network due to gravity, and partially covered on the middle layer network that plays a supporting role. After drying, the outer layer preparation is completed to form a silicon-carbon composite electrode; S4. Roll-pressed composite electrode: Roll the composite electrode according to the compaction density of the outer layer active material to complete the preparation of the silicon-carbon composite electrode.

[0015] Preferably, the middle layer coating method is an intermittent coating method, including horizontal intermittence or longitudinal intermittence, and after coating, the middle layer active material is in strip or dot shape to form a dense middle layer network; the size of one dimension of the minimum unit of the intermittent coating in strip shape is 0.01~5mm, and the size of the other dimension is consistent with the size of the inner layer in this dimension; the minimum unit dot area of ​​the intermittent coating in dot shape is 0.0001~25mm; the preparation of the inner layer and the middle layer includes separate or simultaneous preparation, using a device with a double nozzle to achieve simultaneous coating, and then drying to complete the preparation of the inner layer and the middle layer.

[0016] The present invention also provides a chemical power source, comprising a negative electrode sheet, wherein the negative electrode is the silicon-carbon composite electrode according to claim 1 and is prepared by the preparation method according to claim 2, and the chemical power source comprises a lithium-ion battery or a supercapacitor.

[0017] Compared with the prior art, the present invention has the following advantages: The present invention mixes silicon-carbon material with carbon nanotubes and aqueous binder with water as solvent to form a silicon-carbon inner layer, which is coated on both sides of the current collector, wherein the long-range conductive network of carbon nanotubes has better conductivity, and the aqueous binder forms hydrogen bonds with the silicon-carbon surface to have better bonding properties, which inhibits the expansion of the silicon-carbon inner layer from the formulation level to a certain extent. In addition, by virtue of the fact that the compaction density of the middle-layer carbon-based material is smaller than that of the outer-layer active material, intermittent coating is used to form a dense network, and the outer-layer material is partially embedded in the middle-layer network due to gravity during the coating process, and partially covers the middle-layer surface. Rolling is carried out using the compaction density of the outer-layer active material. The outer-layer active material in the middle-layer network structure cannot be further compacted after the middle-layer carbon-based material reaches the limit compaction density, thereby forming a middle-layer network with a supporting function, and the outer-layer active material embedded therein cannot reach its nominal compaction due to the supporting effect of the middle-layer network, forming a buffer area with a large porosity, which inhibits the expansion of the silicon-carbon electrode from the electrode structure design level. The negative electrode sheet prepared using this type of electrode has a smaller expansion rate and the prepared lithium-ion battery has better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 , is a schematic cross-sectional view of the current collector after coating the inner layer; Figure 2 , is a top view schematic diagram after the current collector is coated on the inner layer; Figure 3 , is a schematic cross-sectional view after coating the strip-shaped middle layer; Figure 4 , is a top view schematic diagram after coating the strip middle layer; Figure 5 , is a schematic diagram of a cross-sectional strip representation of a composite electrode formed after coating the outer layer; Figure 6 , is a schematic diagram of a top view of a composite electrode formed after coating the outer layer; Figure 7 , schematic cross-sectional view of the composite electrode after rolling; Figure 8 , schematic diagram of the cross section after coating the dot-shaped middle layer; Fig. 9 , schematic diagram of top view after coating the dot-shaped middle layer; Fig.10 , schematic diagram of the cross-section dot representation of the composite electrode formed after coating the outer layer; Fig.11 , schematic diagram of a top-down dotted representation of a composite electrode formed after coating the outer layer.

[0019] In the figure: 1. Current collector; 2. Inner silicon-carbon layer; 3. Carbon-based middle layer; 4. Outer active layer; 5. Buffer area. DETAILED DESCRIPTION

[0020] In order to make the purpose, principle and structure of the present invention more clear, it is further described below in conjunction with the drawings and specific embodiments.

[0021] Embodiment 1: This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer, and the coating amount is 200g / m 2 .

[0022] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 10g / m 2 (accounting for 5%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0023] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0024] See also Figure 3 , Figure 4 The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0025] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 10 / 1 * 100.5% * 1 * 40% = 4.02g / m 2 , and then dried to complete the preparation of the middle layer network.

[0026] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-10-4.02 = 185.98 g / m 2During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 10 / 1*100.5%*1*60%=6.03g / m 2 , the outer coating amount covering the middle layer support network = 185.98-6.03 = 179.95g / m 2 , and then dried to complete the preparation of the outer layer.

[0027] See also Figure 7 According to the compaction density of the outer graphite material 1.6g / cm 3 The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 10 / 1.0 = 10um; the nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 4.02 / 1.0 / 40% = 10.05um (also the thickness of the middle graphite embedding layer); the nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 179.95 / 1.6 = 112.46um; the total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 10 + 10.05 + 112.46 = 132.51um. By adopting a nominal compaction density greater than that of the inner and middle layers, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity.

[0028] Calculate the porosity of the middle layer: According to porosity = (mixture true density - pole piece compaction density) / mixture true density * 100%; True density of the material: hard carbon is 1.5g / cm 3 Graphite is 2.24g / cm 3 Carbon nanotubes and conductive carbon black were both 1.5 g / cm 3 Carboxymethyl cellulose is 1.6 g / cm 3 Styrene butadiene rubber is 0.93 g / cm 3 count; True density of hard carbon mixture = 1.5*90%+1.5*4%+1.6*0.5%+0.93*5.5%=1.47 g / cm 3 ; True density of graphite mixture = 2.24*90%+1.5*4%+1.6*0.5%+0.93*5.5%=2.14g / cm 3 ; The porosity of the middle layer hard carbon = (true density of hard carbon mixture - compacted density of hard carbon) / true density of hard carbon mixture * 100% = (1.47-1) / 1.47 * 100% = 32%; The porosity of graphite embedded in the middle network = (true density of graphite mixture - compacted density of middle hard carbon) / true density of graphite mixture * 100% = (2.14-1) / 2.14 * 100% = 53.3%; The porosity of the outer graphite layer = (true density of graphite mixture - compacted density of graphite) / true density of graphite mixture * 100% = (2.14-1.6) / 2.14 * 100% = 25.2%; According to the calculation results, a silicon-carbon composite electrode was constructed by adopting the preparation method of the composite electrode. The inner layer was coated with silicon carbon, and a dense hard carbon network was constructed in the middle layer. Graphite with a higher compaction density was embedded in the middle layer network to form a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0029] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0030] Example 2 (the difference from Example 1 is that the coating of the middle layer is dot-shaped): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer, and the coating amount is 200g / m 2 .

[0031] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 10g / m 2 (accounting for 5%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0032] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0033] See also Figure 8 , Fig. 9The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed to be an intermittently arranged circular nozzle. The intermittent spraying area of ​​the nozzle is designed to have a coating diameter of 2mm, and the maximum spacing of the non-spraying area is designed to be 3mm. The nozzle is intermittently coated with an intermittent distance of 2mm (coating rate is 20.9%) to form a dot-shaped hard carbon network.

[0034] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * coating rate of middle layer network = 10 / 1*100.5%*1*20.9%=2.1g / m 2 , and then dried to complete the preparation of the middle layer network.

[0035] See also Fig.10 , Fig.11 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-10-2.1 = 187.9g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / inner layer silicon carbon compaction density*inner layer silicon carbon expansion rate*middle layer material compaction density*(1-middle layer network coating rate)=10 / 1*100.5%*1*79.1%=7.95g / m 2 , the outer coating amount covering the middle layer support network = 187.9-7.95 = 179.95g / m 2 , and then dried to complete the preparation of the outer layer.

[0036] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 10 / 1.0 = 10um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 2.1 / 1.0 / 20.9% = 10.04um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 179.95 / 1.6 = 112.46um. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 10 + 10.04 + 112.46 = 132.5um. By using a nominal compaction density greater than that of the inner layer and the middle layer, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity. The calculation method of the middle layer porosity is the same as that of Example 1, forming a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0037] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0038] Example 3 (the difference from Example 1 is that the coating amount of the inner layer of silicon carbon is increased): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer. The coating amount is 200g / m 2 .

[0039] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 20g / m 2 (accounting for 10%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0040] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0041] See also Figure 3 , Figure 4The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0042] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 20 / 1 * 100.5% * 1 * 40% = 8.04g / m 2 , and then dried to complete the preparation of the middle layer network.

[0043] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-20-8.04 = 171.96 g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 20 / 1*100.5%*1*60%=12.06g / m 2 , the outer coating amount covering the middle support network = 171.96-12.06 = 159.9g / m 2 , and then dried to complete the preparation of the outer layer.

[0044] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 20 / 1.0 = 20um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 8.04 / 1.0 / 40% = 20.1um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 159.9 / 1.6 = 99.94um. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 10+20.1+99.94=130.04um. By using a nominal compaction density greater than that of the inner layer and the middle layer, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity. The calculation method of the middle layer porosity is the same as that of Example 1, forming a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0045] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0046] Example 4 (the difference from Example 1 is that the coating amount of the inner layer of silicon carbon is increased): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer. The coating amount is 200g / m 2 .

[0047] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 40g / m 2 (accounting for 20%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0048] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0049] See also Figure 3 , Figure 4The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0050] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 40 / 1 * 100.5% * 1 * 40% = 16.08g / m 2 , and then dried to complete the preparation of the middle layer network.

[0051] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-40-16.08 = 143.92g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 40 / 1*100.5%*1*60%=24.12g / m 2 , the outer coating amount covering the middle support network = 143.92-24.12 = 119.8g / m 2 , and then dried to complete the preparation of the outer layer.

[0052] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 40 / 1.0 = 40um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 16.08 / 1.0 / 40% = 40.2um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 119.8 / 1.6 = 74.88um. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 40+40.2+74.88=155.08um. By using a nominal compaction density greater than that of the inner layer and the middle layer, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity. The calculation method of the middle layer porosity is the same as that of Example 1, forming a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0053] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0054] Example 5 (the difference from Example 1 is that the coating amount of the inner layer of silicon carbon is increased): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer. The coating amount is 200g / m 2 .

[0055] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 60g / m 2 (accounting for 30%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0056] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0057] See also Figure 3 , Figure 4The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0058] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 60 / 1*100.5%*1*40%=24.12g / m 2 , and then dried to complete the preparation of the middle layer network.

[0059] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-60-24.12 = 115.88 g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 60 / 1*100.5%*1*60%=36.18g / m 2 The outer layer coating amount covering the middle layer support network = 115.88-36.18 = 79.7g / m2, and then the outer layer is prepared by drying.

[0060] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 60 / 1.0 = 60um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 24.12 / 1.0 / 40% = 60.3um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 79.7 / 1.6 = 49.81um. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 60+60.3+49.81=170.11um. By using a nominal compaction density greater than that of the inner layer and the middle layer, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity. The calculation method of the middle layer porosity is the same as that of Example 1, forming a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0061] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0062] Example 6 (the difference from Example 1 is that the content of silicon in silicon carbon is increased): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer. The coating amount is 200g / m 2 .

[0063] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 40%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 10g / m 2 (accounting for 5%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0064] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 40% + 15% * 60% = 129%.

[0065] See also Figure 3 , Figure 4The middle layer is made of hard carbon, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0066] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 10 / 1*129%*1*40%=5.16g / m 2 , and then dried to complete the preparation of the middle layer network.

[0067] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 90%: 4%: 0.5%: 5.5%. After being evenly mixed, it is coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-10-5.16 = 184.84g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 10 / 1*129%*1*60%=7.74g / m 2 The outer layer coating amount covering the middle layer support network = 184.84-7.74 = 177.1g / m2, and then the outer layer is prepared by drying.

[0068] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 10 / 1.0 = 10um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 5.16 / 1.0 / 40% = 12.9um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 177.1 / 1.6 = 110.69um. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 10+12.9+110.69=133.59um. By using a nominal compaction density greater than that of the inner layer and the middle layer, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thereby having a larger porosity. The calculation method of the middle layer porosity is the same as that of Example 1, forming a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0069] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0070] Example 7 (the difference from Example 1 is that the formulas of the middle layer and the outer layer are adjusted): This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes an inner layer, a middle layer and an outer layer. The coating amount is 200g / m 2 .

[0071] See also Figure 1 , Figure 2 The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil. The coating amount is 10g / m 2 (accounting for 5%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0072] The expansion rate of the inner layer silicon carbon (%) = the theoretical expansion rate of silicon material * the proportion of silicon element + the theoretical expansion rate of carbon material * the proportion of carbon material = 300% * 30% + 15% * 70% = 100.5%.

[0073] See also Figure 3 , Figure 4The middle layer is made of hard carbon, conductive carbon black and polyvinylidene fluoride mixed in a mass ratio of 94%:3%:3%, and then intermittently coated on both sides of the inner layer. The coating nozzle is designed for intermittent coating. The intermittent spraying area of ​​the nozzle is designed to have a coating width of 2mm, and the non-spraying area is designed to be 3mm (the coating rate is 40%). The nozzle is used for uninterrupted coating to form a strip-shaped hard carbon network.

[0074] Coating amount of middle layer hard carbon network (g / m 2 ) = inner layer coating amount / inner layer silicon carbon compaction density * inner layer silicon carbon expansion rate * middle layer material compaction density * middle layer network coating rate = 10 / 1 * 100.5% * 1 * 40% = 4.02g / m 2 , and then dried to complete the preparation of the middle layer network.

[0075] See also Figure 5 , Figure 6 The outer layer is made of graphite, conductive carbon black, and polyvinylidene fluoride mixed in a mass ratio of 92%:4%:4% and then coated on both sides of the middle layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount - the middle layer coating amount = 200-10-4.02 = 185.98g / m 2 During the coating process of the outer electrode, the active layer slurry is partially embedded in the middle layer network due to gravity. The coating amount embedded in the middle layer network = inner layer coating amount / compaction density of inner layer silicon carbon * expansion rate of inner layer silicon carbon * compaction density of middle layer material * (1-coating rate of middle layer network) = 10 / 1*100.5%*1*60%=6.03g / m 2 , the outer coating amount covering the middle layer support network = 185.98-6.03 = 179.95g / m 2 , and then dried to complete the preparation of the outer layer.

[0076] According to the compaction density of the outer graphite material 1.6g / cm 3The composite electrode is rolled to complete the preparation of the silicon-carbon composite electrode. The nominal thickness of the inner silicon-carbon layer = the inner coating amount / the compacted density of the inner silicon-carbon material = 10 / 1.0 = 10um. The nominal thickness of the middle hard carbon layer is the middle coating amount / the compacted density of the middle hard carbon material / the middle coating rate = 4.02 / 1.0 / 40% = 10.05um (also the thickness of the middle graphite embedding layer). The nominal thickness of the outer graphite layer = the outer coating amount / the compacted density of the outer graphite material = 179.95 / 1.6 = 112.47. The total thickness of the electrode active layer = the inner layer thickness + the middle layer thickness + the outer layer thickness = 10 + 10.05 + 112.47 = 132.52um. Using a nominal compaction density greater than that of the inner and middle layers, the thickness cannot be further reduced after reaching the nominal thickness, and the graphite embedded in the middle layer is supported by the hard carbon middle layer network and cannot reach its nominal thickness, thus having a larger porosity. The porosity of the middle layer is calculated as: According to porosity = (mixture true density - pole piece compaction density) / mixture true density * 100% True density of the material: hard carbon is 1.5g / cm 3 Graphite is 2.24 g / cm 3 Carbon nanotubes and conductive carbon black were both 1.5 g / cm 3 Carboxymethyl cellulose is 1.6 g / cm 3 Styrene butadiene rubber is 0.93 g / cm 3 PVDF is 1.78g / cm 3 count.

[0077] True density of hard carbon mixture = 1.5*94%+1.5*3%+1.78*3%=1.51g / cm 3 ; True density of graphite mixture = 2.24*92%+1.5*4%+1.78*4%=2.19 g / cm 3 ; The porosity of the middle layer hard carbon = (true density of hard carbon mixture - compacted density of hard carbon) / true density of hard carbon mixture * 100% = (1.51-1) / 1.51 * 100% = 33.8%; The porosity of graphite embedded in the middle network = (true density of graphite mixture - compacted density of middle hard carbon) / true density of graphite mixture * 100% = (2.19-1) / 2.19 * 100% = 54.3%; The porosity of the outer graphite layer = (true density of graphite mixture - compacted density of graphite) / true density of graphite mixture * 100% = (2.19-1.6) / 2.19 * 100% = 26.9%; According to the calculation results, a silicon-carbon composite electrode was constructed by adopting the preparation method of the composite electrode. The inner layer was coated with silicon carbon, and a dense hard carbon network was constructed in the middle layer. Graphite with a higher compaction density was embedded in the middle layer network to form a graphite middle layer with a larger porosity, thereby providing space for the expansion of silicon carbon.

[0078] This silicon-carbon composite electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0079] Embodiment 8 (comparative example): This comparative example provides a silicon-based material and a preparation method thereof, which are compared with the above-mentioned embodiment. The composite silicon-based material comprises an inner layer and an outer layer. The coating amount is 200g / m2.

[0080] The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil with a coating amount of 10g / m 2 (accounting for 5%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0081] The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber mixed in a mass ratio of 90%: 4%: 0.5%: 5.5% and then applied to both sides of the inner layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount = 200-10 = 190g / m 2 , and then dried to complete the preparation of the outer layer.

[0082] According to the compaction density of the outer graphite material 1.6g / cm 3 The silicon carbon electrode is rolled to complete the preparation of the silicon carbon electrode. The nominal thickness of the inner silicon carbon layer = the inner layer coating amount / the compaction density of the inner silicon carbon material = 10 / 1.0 = 10um. The nominal thickness of the outer graphite layer is the outer layer coating amount / the compaction density of the outer graphite material = 190 / 1.6 = 118.75um. The total thickness of the electrode active layer = the inner layer thickness + the outer layer thickness = 10 + 118.75 = 128.75um.

[0083] This silicon-carbon electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0084] Embodiment 9 (comparative example): This comparative example provides a silicon-based material and a preparation method thereof, which is compared with the above-mentioned embodiment. The composite silicon-based material comprises an inner layer and an outer layer. The coating amount is 200g / m 2 .

[0085] The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil with a coating amount of 20g / m 2 (accounting for 10%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0086] The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber mixed in a mass ratio of 90%: 4%: 0.5%: 5.5%, and then coated on both sides of the inner layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount = 200-20 = 180g / m 2 , and then dried to complete the preparation of the outer layer.

[0087] According to the compaction density of the outer graphite material 1.6g / cm 3 The silicon carbon electrode is rolled to complete the preparation of the silicon carbon electrode. The nominal thickness of the inner silicon carbon layer = the inner layer coating amount / the compaction density of the inner silicon carbon material = 20 / 1.0 = 20um. The nominal thickness of the outer graphite layer is the outer layer coating amount / the compaction density of the outer graphite material = 180 / 1.6 = 112.5um. The total thickness of the electrode active layer = the inner layer thickness + the outer layer thickness = 20+112.5 = 132.5um.

[0088] This silicon-carbon electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0089] Embodiment 10 (comparative example): This comparative example provides a silicon-based material and a preparation method thereof, which is compared with the above-mentioned embodiment. The composite silicon-based material comprises an inner layer and an outer layer. The coating amount is 200g / m 2 .

[0090] The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil with a coating amount of 40g / m 2 (accounting for 20%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0091] The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber mixed in a mass ratio of 90%: 4%: 0.5%: 5.5%, and then coated on both sides of the inner layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount = 200-40 = 160g / m 2 , and then dried to complete the preparation of the outer layer.

[0092] According to the compaction density of the outer graphite material 1.6g / cm 3 The silicon carbon electrode is rolled to complete the preparation of the silicon carbon electrode. The nominal thickness of the inner silicon carbon layer = the inner layer coating amount / the compaction density of the inner silicon carbon material = 40 / 1.0 = 40um. The nominal thickness of the outer graphite layer is the outer layer coating amount / the compaction density of the outer graphite material = 160 / 1.6 = 100um. The total thickness of the electrode active layer = the inner layer thickness + the outer layer thickness = 40+100 = 140um.

[0093] This silicon-carbon electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0094] Embodiment 11 (comparative example): This comparative example provides a silicon-based material and a preparation method thereof, which is compared with the above-mentioned embodiment. The composite silicon-based material comprises an inner layer and an outer layer. The coating amount is 200g / m 2 .

[0095] The inner layer is made of silicon-carbon material (silicon content is 30%), single-walled carbon nanotubes, and acrylic acid in a mass ratio of 90%:5%:5% and then coated on both sides of the copper foil with a coating amount of 60g / m 2 (accounting for 30%), the coating width is 200mm, and then the inner layer is prepared after drying.

[0096] The outer layer is made of graphite, conductive carbon black, carboxymethyl cellulose, and styrene-butadiene rubber mixed in a mass ratio of 90%: 4%: 0.5%: 5.5% and then coated on both sides of the inner layer. The coating amount = the designed total electrode coating amount - the inner layer coating amount = 200-60 = 140g / m 2 , and then dried to complete the preparation of the outer layer.

[0097] According to the compaction density of the outer graphite material 1.6g / cm 3The silicon carbon electrode is rolled to complete the preparation of the silicon carbon electrode. The nominal thickness of the inner silicon carbon layer = the inner layer coating amount / the compaction density of the inner silicon carbon material = 60 / 1.0 = 60um. The nominal thickness of the outer graphite layer is the outer layer coating amount / the compaction density of the outer graphite material = 140 / 1.6 = 87.5um. The total thickness of the electrode active layer = the inner layer thickness + the outer layer thickness = 60+87.5=147.5um.

[0098] This silicon-carbon electrode is used as the negative electrode, and is prepared into a battery cell through stamping, lamination or winding. The preparation of the lithium-ion battery is completed through welding, drying, shelling, liquid injection, infiltration, formation, aging and other processes. The cycle performance and expansion rate of the electrode are shown in Table 1.

[0099] Table 1 The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes according to the technical solutions and novel concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A silicon-carbon composite electrode, characterized in that: include: current collector; a silicon carbon inner layer disposed on the current collector; A supporting buffer middle layer disposed on the silicon carbon inner layer; an outer layer of active material disposed on the supporting and buffering middle layer; The compaction density of the supporting buffer middle layer is less than the compaction density of the active material outer layer, and the supporting buffer middle layer forms a network structure, and part of the active material outer layer is embedded in the network structure.

2. A silicon-carbon composite electrode as claimed in claim 1, characterized in that The silicon-carbon inner layer is completely coated on the current collector and is composed of a silicon-carbon material, a conductive agent, and a binder. The silicon-carbon material includes one silicon-carbon material or a combination of multiple silicon-carbon materials, wherein the content of silicon element in each silicon-carbon material does not exceed 50%, and the proportion of the silicon-carbon material to the total active substance is ≤30%. The conductive agent includes carbon nanotubes or carbon black or a combination of the above. The binder is an aqueous binder, and the solvent used is deionized water; the carbon black includes conductive carbon black, Ketjen black, acetylene black or any combination of the above. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes or any combination thereof. The aqueous binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane or any combination of the above.

3. A silicon-carbon composite electrode as claimed in claim 1, characterized in that The supporting buffer middle layer is composed of a carbon-based material, a conductive agent, and a binder. The carbon-based material includes hard carbon, soft carbon or any combination thereof. The compaction density of the carbon-based material is ≥ the silicon carbon used in the silicon-carbon inner layer and is less than the active material used in the active material outer layer. The conductive agent includes carbon nanotubes, carbon black or any combination thereof. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes or any combination thereof. The carbon black includes conductive carbon black, Ketjen black, acetylene black or any combination thereof. The binder includes a water-based binder and an oil-based binder.

4. A silicon-carbon composite electrode as claimed in claim 1 or 3, characterized in that After coating, the supporting buffer middle layer presents a dense network structure, including a transverse network and a longitudinal network. The coating rate of the supporting buffer middle layer network is ≤50%, and the coating rate of the supporting buffer middle layer network is the total coating area of ​​the middle layer / the total coating area of ​​the inner layer; the water-based binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane or any combination thereof, and the oil-based binder includes polyvinylidene fluoride, polyimide, perfluorosulfonic acid ionomer or any combination thereof.

5. A silicon-carbon composite electrode as claimed in claim 4, characterized in that The coating amount of the supporting buffer middle layer network = the coating amount of the inner layer / the compaction density of the inner layer silicon carbon * the maximum expansion rate of the inner layer silicon carbon * the compaction density of the middle layer material * the coating rate of the middle layer network.

6. A silicon-carbon composite electrode as claimed in claim 1, characterized in that The outer layer of the active material is composed of an active material, a conductive agent, and a binder. The active material includes graphite, soft carbon, and mesophase carbon microspheres. The conductive agent includes carbon nanotubes, carbon black, or any combination thereof. The carbon nanotubes include single-walled carbon nanotubes, multi-walled carbon nanotubes, whisker carbon nanotubes, or any combination thereof. The carbon black includes conductive carbon black, Ketjen black, acetylene black, or any combination thereof. The binder includes an aqueous binder and an oil-based binder. The aqueous binder includes acrylonitrile, acrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, water-based polyurethane, or any combination thereof. The oil-based binder includes polyvinylidene fluoride, polyimide, perfluorosulfonic acid ionomer, or any combination thereof.

7. A silicon-carbon composite electrode as claimed in claim 1 or 6, characterized in that The outer layer of active material is composed of active materials with a compaction density higher than that of the supporting buffer middle layer, and the coating amount of the outer layer = the designed total coating amount of the electrode - the coating amount of the inner layer - the coating amount of the middle layer.

8. A method for preparing a silicon-carbon composite electrode as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1. Inner layer preparation: Silicon-carbon material, conductive agent, and binder are mixed evenly in a mass ratio of (60-97.5%): (0.5-30%): (2-10%), and then coated on both sides of the current collector, which is copper foil. After drying, the inner layer preparation is completed; S2. Preparation of middle layer: Mix the carbon-based material, conductive agent and binder in a mass ratio of (90-99%): (0-5%): (1-5%), and then apply them intermittently on both sides of the pole piece after the inner layer is prepared. After drying, the preparation of the middle layer is completed. The coating nozzle for coating the middle layer can be designed as an intermittent nozzle, and the coating nozzle has the function of intermittent coating; S3. Preparation of outer layer: Active material, conductive agent and binder are mixed evenly in a mass ratio of (90~98.5%): (0.5~5%): (1~5%), and then coated on both sides of the electrode sheet after the middle layer preparation is completed. During the coating process of the outer layer electrode sheet, the active layer slurry is partially embedded in the middle layer network due to gravity, and partially covered on the middle layer network that plays a supporting role. After drying, the outer layer preparation is completed to form a silicon-carbon composite electrode; S4. Rolling the composite electrode: Rolling the composite electrode according to the compaction density of the outer layer active material to complete the preparation of the silicon-carbon composite electrode.

9. The method for preparing a silicon-carbon composite electrode according to claim 7, characterized in that The middle layer coating method is an intermittent coating method, including horizontal intermittent or vertical intermittent, and after coating, the middle layer active material is in strip or dot shape to form a dense middle layer network; The intermittently coated strip-shaped minimum unit has a dimension of 0.01 to 5 mm, and the other dimension is consistent with the dimension of the inner layer; The minimum unit dot area of ​​the intermittent coating is 0.0001-25 mm; The preparation of the inner layer and the middle layer can be performed separately or simultaneously, and a device with a double nozzle is used to achieve simultaneous coating, and then drying is performed to complete the preparation of the inner layer and the middle layer.

10. A chemical power source, comprising a negative electrode sheet, characterized in that: The negative electrode is the silicon-carbon composite electrode according to claim 1 and is prepared by the preparation method according to claim 2, and the chemical power source includes a lithium-ion battery or a supercapacitor.